NLRP3 inflammasome in atherosclerosis: Mechanisms and targeted therapies - Pengfei Chen; Xia Li; Xia Li (Frontiers Media S.A., 2024)
Atherosclerosis (AS) is the primary pathology behind various cardiovascular diseases and the leading cause of death and disability globally. Recent evidence suggests that AS is a chronic vascular inflammatory disease caused by multiple factors. In this context, the NLRP3 inflammasome, acting as a signal transducer of the immune system, plays a critical role in the onset and progression of AS. The NLRP3 inflammasome is involved in endothelial injury, foam cell formation, and pyroptosis in AS. Therefore, targeting the NLRP3 inflammasome offers a new treatment strategy for AS. This review highlights the latest insights into AS pathogenesis and the pharmacological therapies targeting the NLRP3 inflammasome, focusing on optimal targets for small molecule inhibitors. These insights are valuable for rational drug design and the pharmacological assessment of new targeted NLRP3 inflammasome inhibitors in treating AS.